Life satisfaction and job insecurity: Evidence from Albania - Elvisa Drishti; Fiona Carmichael (Global Labor Organization (GLO), 2022)
Fear of the threat of job loss is likely to elicit negative thoughts that have adverse consequences for not only job satisfaction, but also, all-round happiness and satisfaction with life. Using nationally representative cross-sectional data, this study provides evidence of the negative effect of perceived job insecurity on life satisfaction in post-communist Albania, an under-research context. This adverse effect is found to be more pronounced for women and for blue-collar workers: being in a blue-collar job is associated with lower overall life satisfaction, but if this job is perceived as insecure, the negative effect on life satisfaction is magnified. In contrast, workers in well-paying jobs are more satisfied with their lives and, relatedly, higher education also has a positive impact, more so for males. Evidence of the quality of life effects of job insecurity can be used to inform workplace policy initiatives and practices, particularly as measures of life satisfaction, well-being and happiness are increasingly considered appropriate indicators of social progress and the ultimate goal of public policy.
Keywords: 330; job insecurity; life satisfaction; Albania; well-being; post-communist